1998
DOI: 10.1002/mds.870130617
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral painful legs and moving toes syndrome with moving fingers—evidence for distinct oscillators

Abstract: This case report presents a patient with painful legs and moving toes on the right side followed by the development of involuntary movements in his right hand. The frequencies of the semirhythmic muscle activities in both extremities were different. This finding excludes one central pacemaker for both and supports the notion that separate oscillators in the segmental interneuron pool of different spinal areas may drive the individual movements in this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
2
15
1
Order By: Relevance
“…1 Since then, few cases have been reported, generally in patients with peripheral nerve, plexus, or root disease. [2][3][4] Deep aching or pulling pain often precedes movements by several months. Involuntary movements are composed of complex sequences of flexion/extension and abduction/adduction, which cannot be imitated.…”
mentioning
confidence: 99%
“…1 Since then, few cases have been reported, generally in patients with peripheral nerve, plexus, or root disease. [2][3][4] Deep aching or pulling pain often precedes movements by several months. Involuntary movements are composed of complex sequences of flexion/extension and abduction/adduction, which cannot be imitated.…”
mentioning
confidence: 99%
“…Since then painful limbs/moving extremities has been identified as a syndrome with many variants (painless [7] , unilateral [8] , involving only arms [4] , only legs [1] or both [8] ).…”
Section: Discussionmentioning
confidence: 99%
“…Ebersbach et al 15 reported a patient with unilateral PLMT who 2 months later developed involuntary finger movements in the ipsilateral hand. The authors suspected separate central oscillators for toe and finger movements based on hand and foot EMG asynchrony.…”
Section: And Thementioning
confidence: 99%